Micron-sized iron-nickel alloy magnetic powder and preparation method and application thereof
By adding modified microsilicon powder to the micron-scale iron-nickel alloy magnetic powder and ball milling, annealing, passivation and insulation coating, the problem of difficult to optimize magnetic permeability and loss in the prior art is solved, and the performance of high-efficiency and low-loss magnetic powder is achieved, and the process flow is simplified.
Patent Information
- Application Number
- CN202311252446.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to simultaneously improve magnetic permeability, reduce losses, improve DC bias performance and fluidity in micron-scale iron-nickel alloy magnetic powder, and the process flow is complex and difficult to promote on a large scale.
Micron-scale iron-nickel alloy magnetic powder was prepared by adding modified microsilicon powder to the iron-nickel alloy raw powder for ball milling and annealing, followed by passivation and insulation coating.
It effectively improves the resistivity and permeability of iron-nickel alloy magnetic powder, reduces losses, improves DC bias performance and fluidity, simplifies the process flow, and is suitable for large-scale applications.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnetic materials and relates to an iron-nickel alloy magnetic powder, in particular to a micron-level iron-nickel alloy magnetic powder and a preparation method and application thereof. Background Art
[0002] In the traditional thermal power generation method, in the process of converting mechanical energy into electrical energy, suitable magnetic materials help to efficiently utilize energy and reduce losses in the power generation process. However, due to their low resistance, traditional magnetic materials are prone to produce large eddy current losses as the frequency increases during use, and are difficult to use at high frequencies.
[0003] With the development of miniaturization and high frequency of power electronic equipment, magnetic devices are constantly improving in the direction of high frequency, high power, low power consumption and good electromagnetic compatibility. High magnetic permeability can broaden the application range of devices, low loss can consume less energy, and avoid the degradation of composite material performance caused by loss and heat.
[0004] In recent years, iron-nickel alloy soft magnetic composite materials have been widely used in the preparation of magnetic components because of their high saturation flux density, low core loss, high energy storage and excellent DC bias capability. Magnetic devices made of iron-nickel materials can work under high power, high DC bias or high frequency AC, such as motors, transmissions, transformers, electronic products and other fields.
[0005] Among them, micron-sized ultrafine iron-nickel alloy powder magnetic materials have attracted widespread attention due to their larger surface area and magnetic properties that are different from those of conventional iron-nickel alloy powders. As a magnetic material with a micron structure, micron-sized iron-nickel alloy magnetic powders have special properties that are different from conventional iron-nickel materials. Therefore, they have good potential application value in the fields of high-density magnetic materials, magnetic fluids, electromagnetic shielding materials, and high-efficiency catalysts, and have received increasing attention.
[0006] The particle size of commonly used iron-nickel alloy magnetic powder is usually above 30μm, while the particle size of micron material ultrafine iron-nickel alloy magnetic powder material is 1μm~5μm. In comparison, it has a larger specific surface area and smaller particle size, which can better reduce eddy current losses under high-frequency use and improve the performance of DC superposition. However, its low resistivity also affects the application of this material in the electromagnetic field. After all, using too much coating agent will affect the high saturation magnetic induction intensity performance of the material itself.
[0007] CN 115985614A discloses a low-loss iron-nickel soft magnetic powder and a preparation method thereof. The performance of the magnetic powder is improved by preparing a new insulating agent, mixing and heating epichlorohydrin, terminal hydroxyl monomer and isopropyl alcohol, adding tetraethylammonium bromide to reflux and stir, then cooling and adding sodium hydroxide aqueous solution to stir, and then vacuum distilling to obtain a crude product after the reaction is completed, then adding methyl isobutyl ketone and sodium hydroxide aqueous solution to the crude product, heating and stirring to mix, filtering and removing salt residue, heating pure water to wash to neutrality, standing, separating the water layer, vacuum distilling, finally washing with n-hexane, vacuum drying to constant weight, obtaining a modified epoxy resin, and finally mixing the modified epoxy resin with a curing agent to obtain an insulating agent. The insulating agent prepared by the above preparation method can effectively improve the resistance of the iron-nickel magnetic powder, but the overall process flow is relatively complicated, and the amount of insulating agent required for the micron-level iron-nickel powder with a relatively large surface area is relatively large, which is easy to weaken the high saturation magnetic induction intensity of the magnetic powder itself.
[0008] CN 114156034A discloses a low-loss iron-nickel magnetic powder core composite coating method, which comprises the following steps: surface-treating iron and nickel respectively and then coating them with silicon dioxide, then mixing the two in proportion, coating them with epoxy-modified organic silicone resin solution, adding lubricant, pressing and forming, and heat-treating to obtain a low-loss iron-nickel magnetic powder core. The above preparation method can improve the magnetic permeability of the magnetic powder core and effectively reduce the loss, but the overall applicable pressing conditions are relatively harsh, the applicable magnetic powder particle size is relatively large, and it is difficult to apply to finer magnetic powder.
[0009] It can be seen that how to provide a micron-sized iron-nickel alloy magnetic powder and a preparation method thereof, improve the magnetic permeability of the magnetic powder core while reducing the loss, improve the DC bias performance and the fluidity of the magnetic powder, and simplify the process flow has become an urgent problem that technical personnel in this field need to solve. Summary of the invention
[0010] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a micron-sized iron-nickel alloy magnetic powder and a preparation method and application thereof. The preparation method improves the magnetic permeability of the magnetic powder core while reducing the loss, improves the DC bias performance and the fluidity of the magnetic powder, simplifies the process flow, and is conducive to large-scale promotion and application.
[0011] To achieve this object, the present invention adopts the following technical solutions:
[0012] In a first aspect, the present invention provides a method for preparing micron-sized iron-nickel alloy magnetic powder, the preparation method comprising the following steps:
[0013] (1) obtaining an iron-nickel alloy raw powder having a particle size of micrometer level;
[0014] (2) mixing a silane coupling agent, an organic solvent and microsilica powder, stirring them evenly, and then heating and performing alcoholysis until the solvent is completely volatilized to obtain modified microsilica powder;
[0015] (3) mixing the original iron-nickel alloy powder and the modified microsilicon powder, ball milling, and annealing to obtain an intermediate powder;
[0016] (4) The intermediate powder is subjected to passivation treatment and insulation coating in sequence to obtain micron-sized iron-nickel alloy magnetic powder.
[0017] There is no particular order in which steps (1) and (2) are performed.
[0018] The preparation method provided by the present invention adds modified micro silicon powder into the original iron-nickel alloy powder, thereby reducing the negative influence on the high saturation magnetic induction intensity performance of the micron-level magnetic powder, and effectively improving the resistivity of the iron-nickel alloy magnetic powder. The obtained micron-level magnetic powder has good insulation, low loss, high magnetic permeability, and excellent DC bias performance. The magnetic powder is easy to flow, which is conducive to subsequent pressing and molding. At the same time, the preparation process is simple, which is conducive to large-scale promotion and application.
[0019] Preferably, the average particle size of the iron-nickel alloy raw powder in step (1) is 4-6 μm, for example, it can be 4 μm, 4.2 μm, 4.4 μm, 4.6 μm, 4.8 μm, 5 μm, 5.2 μm, 5.4 μm, 5.6 μm, 5.8 μm or 6 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0020] Preferably, the iron content in the iron-nickel alloy raw powder in step (1) is 45-55wt%, for example, it can be 45wt%, 46wt%, 47wt%, 48wt%, 49wt%, 50wt%, 51wt%, 52wt%, 53wt%, 54wt% or 55wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] Preferably, the nickel content in the iron-nickel alloy raw powder in step (1) is 45-55wt%, for example, it can be 45wt%, 46wt%, 47wt%, 48wt%, 49wt%, 50wt%, 51wt%, 52wt%, 53wt%, 54wt% or 55wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0022] Preferably, the content of impurity metals in the iron-nickel alloy raw powder in step (1) is ≤1.5wt%, for example, it can be 0.2wt%, 0.4wt%, 0.6wt%, 0.8wt%, 1wt%, 1.2wt%, 1.4wt% or 1.5wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0023] Preferably, the mixing method in step (2) includes: first adding the silane coupling agent into the organic solvent and stirring to dissolve, and then adding the microsilica powder into the organic solvent and stirring evenly.
[0024] Preferably, based on the mass of the iron-nickel alloy raw powder, the amount of the silane coupling agent used in step (2) is 1-3wt%, for example, it can be 1wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt%, 2wt%, 2.2wt%, 2.4wt%, 2.6wt%, 2.8wt% or 3wt%, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0025] Preferably, based on the mass of the iron-nickel alloy raw powder, the amount of the organic solvent used in step (2) is 4-6wt%, for example, it can be 4wt%, 4.2wt%, 4.4wt%, 4.6wt%, 4.8wt%, 5wt%, 5.2wt%, 5.4wt%, 5.6wt%, 5.8wt% or 6wt%, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0026] Preferably, based on the mass of the iron-nickel alloy raw powder, the amount of the microsilicon powder in step (2) is 1-3wt%, for example, it can be 1wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt%, 2wt%, 2.2wt%, 2.4wt%, 2.6wt%, 2.8wt% or 3wt%, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0027] In the present invention, the amount of microsilicon powder needs to be controlled within a reasonable range. When the amount is less than 1wt%, too little microsilicon powder cannot sufficiently improve the resistivity; when the amount is higher than 3wt%, too much microsilicon powder will reduce the content of iron and nickel powder in the magnetic powder core, thereby significantly reducing the magnetic permeability performance.
[0028] Preferably, the silane coupling agent in step (2) comprises isocyanate silane.
[0029] Preferably, the organic solvent in step (2) comprises acetone.
[0030] Preferably, the average particle size of the microsilica powder in step (2) is 0.1-1 μm, for example, it can be 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm or 1 μm, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] Preferably, the method of heating alcoholysis in step (2) comprises: heating the uniformly stirred solvent to a target temperature, and adding anhydrous ethanol dropwise while stirring.
[0032] The present invention carries out alcoholysis at elevated temperature because the microsilica powder needs to undergo dehydration, condensation and curing reactions with the alcoholysed silane coupling agent under dynamic heating conditions to achieve the purpose of modifying the microsilica powder.
[0033] Preferably, the target temperature is 100-120°C, for example, it can be 100°C, 102°C, 104°C, 106°C, 108°C, 110°C, 112°C, 114°C, 116°C, 118°C or 120°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] Preferably, based on the mass of the iron-nickel alloy raw powder, the amount of anhydrous ethanol used is 2-5wt%, for example, it can be 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] Preferably, the ball milling time in step (3) is 20-40 min, for example, it can be 20 min, 22 min, 24 min, 26 min, 28 min, 30 min, 32 min, 34 min, 36 min, 38 min or 40 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] Preferably, the annealing treatment in step (3) is carried out in a nitrogen-hydrogen mixed atmosphere.
[0037] Preferably, the volume fraction of hydrogen in the nitrogen-hydrogen mixed atmosphere is ≥20%, for example, it can be 20%, 25%, 30%, 35%, 40%, 45% or 50%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] Preferably, the temperature of the annealing treatment in step (3) is 400-600°C, for example, it can be 400°C, 420°C, 440°C, 460°C, 480°C, 500°C, 520°C, 540°C, 560°C, 580°C or 600°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0039] In the present invention, the temperature of the annealing treatment needs to be limited to a reasonable range. When the temperature is lower than 400°C, the too low annealing temperature cannot achieve the purpose of reducing the coercivity of the magnetic powder and improving the overall performance of the magnetic powder through annealing; when the temperature is higher than 600°C, although the too high temperature will reduce the coercivity of the magnetic powder more, it will also have a relatively obvious negative impact on the loss performance and DC superposition performance of the magnetic powder.
[0040] Preferably, the annealing time in step (3) is 1-4 h, for example, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h or 4 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] Preferably, the passivation treatment in step (4) comprises the following steps:
[0042] (4.1.1) mixing phosphoric acid and acetone to obtain a passivation solution;
[0043] (4.1.2) Mix the intermediate powder and the passivation solution, stir evenly, and then heat to the first temperature until the solvent is completely evaporated to obtain a passivation powder.
[0044] Preferably, the insulating coating in step (4) comprises the following steps:
[0045] (4.2.1) mixing a binder, a curing agent and acetone to obtain a bonding solution;
[0046] (4.2.2) mixing the passivation powder and the bonding solution, stirring evenly, and heating to a second temperature until the solvent is completely volatilized to obtain a bonding powder;
[0047] (4.2.3) The mixed bonding powder and the release agent are ball-milled to obtain micron-sized iron-nickel alloy magnetic powder.
[0048] Preferably, based on the mass of the intermediate powder, the amount of phosphoric acid used in step (4.1.1) is 0.5-2wt%, for example, it can be 0.5wt%, 0.6wt%, 0.8wt%, 1wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt% or 2wt%, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0049] Preferably, based on the mass of the intermediate powder, the amount of acetone used in step (4.1.1) is 8-12wt%, for example, 8wt%, 8.5wt%, 9wt%, 9.5wt%, 10wt%, 10.5wt%, 11wt%, 11.5wt% or 12wt%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0050] Preferably, the stirring temperature in step (4.1.2) is 30-50°C, for example, it can be 30°C, 32°C, 34°C, 36°C, 38°C, 40°C, 42°C, 44°C, 46°C, 48°C or 50°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0051] Preferably, the stirring time in step (4.1.2) is 4-6 min, for example, it can be 4 min, 4.2 min, 4.4 min, 4.6 min, 4.8 min, 5 min, 5.2 min, 5.4 min, 5.6 min, 5.8 min or 6 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0052] Preferably, the first temperature in step (4.1.2) is 100-140°C, for example, it can be 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C or 140°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0053] Preferably, based on the mass of the passivation powder, the amount of the binder used in step (4.2.1) is 1-3wt%, for example, it can be 1wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt%, 2wt%, 2.2wt%, 2.4wt%, 2.6wt%, 2.8wt% or 3wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] Preferably, based on the mass of the passivation powder, the amount of the curing agent in step (4.2.1) is 0.3-0.5wt%, for example, it can be 0.3wt%, 0.32wt%, 0.34wt%, 0.36wt%, 0.38wt%, 0.4wt%, 0.42wt%, 0.44wt%, 0.46wt%, 0.48wt% or 0.5wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0055] Preferably, based on the mass of the passivation powder, the amount of acetone used in step (4.2.1) is 8-12wt%, for example, 8wt%, 8.5wt%, 9wt%, 9.5wt%, 10wt%, 10.5wt%, 11wt%, 11.5wt% or 12wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0056] Preferably, the binder in step (4.2.1) comprises any one of epoxy resin, silicone resin or phenolic resin, or a combination of at least two of them. Typical but non-limiting combinations include a combination of epoxy resin and silicone resin, a combination of silicone resin and phenolic resin, a combination of epoxy resin and phenolic resin, or a combination of epoxy resin, silicone resin and phenolic resin.
[0057] Preferably, the curing agent in step (4.2.1) includes m-xylidine.
[0058] Preferably, the stirring time in step (4.2.2) is 8-12 min, for example, it can be 8 min, 8.5 min, 9 min, 9.5 min, 10 min, 10.5 min, 11 min, 11.5 min or 12 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0059] Preferably, the second temperature in step (4.2.2) is 40-60°C, for example, 40°C, 42°C, 44°C, 46°C, 48°C, 50°C, 52°C, 54°C, 56°C, 58°C or 60°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0060] Preferably, based on the mass of the bonding powder, the amount of the release agent used in step (4.2.3) is 0.1-1wt%, for example, it can be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt% or 1wt%, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0061] Preferably, the release agent in step (4.2.3) includes any one of zinc stearate, magnesium stearate, aluminum stearate, calcium stearate or graphite powder, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of zinc stearate and magnesium stearate, a combination of magnesium stearate and aluminum stearate, a combination of aluminum stearate and calcium stearate, a combination of calcium stearate and graphite powder, a combination of zinc stearate, magnesium stearate and aluminum stearate, a combination of magnesium stearate, aluminum stearate and calcium stearate, or a combination of aluminum stearate, calcium stearate and graphite powder.
[0062] Preferably, the ball milling time in step (4.2.3) is 20-40 min, for example, it can be 20 min, 22 min, 24 min, 26 min, 28 min, 30 min, 32 min, 34 min, 36 min, 38 min or 40 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0063] As a preferred technical solution of the first aspect of the present invention, the preparation method comprises the following steps:
[0064] (1) obtaining a micron-sized iron-nickel alloy raw powder with an average particle size of 4-6 μm, wherein the iron content of the iron-nickel alloy raw powder is 45-55 wt %, the nickel content is 45-55 wt %, and the content of impurity metals is ≤1.5 wt %;
[0065] (2) Based on the mass of the iron-nickel alloy raw powder, 1-3wt% of isocyanate silane is first added to 4-6wt% of acetone and stirred to dissolve, and then 1-3wt% of microsilica powder with an average particle size of 0.1-1μm is added to the acetone and stirred evenly, the solvent is heated to 100-120°C, and 2-5wt% of anhydrous ethanol is added dropwise while stirring until the solvent is completely volatilized to obtain modified microsilica powder;
[0066] (3) mixing the original iron-nickel alloy powder and the modified microsilicon powder and ball milling for 20-40 minutes, annealing in a nitrogen-hydrogen mixed atmosphere with a hydrogen volume fraction of ≥20%, and annealing at a temperature of 400-600° C. for 1-4 hours to obtain an intermediate powder;
[0067] (4.1) The intermediate powder is passivated, specifically comprising the following steps:
[0068] (4.1.1) Based on the mass of the intermediate powder, 0.5-2 wt % phosphoric acid and 8-12 wt % acetone are mixed to obtain a passivation solution;
[0069] (4.1.2) mixing the intermediate powder and the passivation solution, stirring at 30-50° C. for 4-6 minutes, and then heating to 100-140° C. until the solvent is completely evaporated to obtain a passivation powder;
[0070] (4.2) Insulating and coating the passivated powder, specifically comprising the following steps:
[0071] (4.2.1) Based on the mass of the passivation powder, 1-3 wt% of a binder, 0.3-0.5 wt% of m-xylidine and 8-12 wt% of acetone are mixed to obtain a bonding solution; the binder comprises any one of epoxy resin, silicone resin or phenolic resin or a combination of at least two thereof;
[0072] (4.2.2) mixing the passivation powder and the bonding solution, stirring for 8-12 minutes and then heating to 40-60° C. until the solvent is completely evaporated to obtain a bonding powder;
[0073] (4.2.3) Based on the mass of the bonding powder, the bonding powder is mixed with 0.1-1wt% of a release agent and ball-milled for 20-40 minutes to obtain micron-sized iron-nickel alloy magnetic powder; the release agent includes any one of zinc stearate, magnesium stearate, aluminum stearate, calcium stearate or graphite powder, or a combination of at least two of them.
[0074] There is no particular order in which steps (1) and (2) are performed.
[0075] In a second aspect, the present invention provides a micron-sized iron-nickel alloy magnetic powder, which is prepared by the preparation method described in the first aspect.
[0076] In a third aspect, the present invention provides an application of the micron-sized iron-nickel alloy magnetic powder as described in the second aspect, wherein the micron-sized iron-nickel alloy magnetic powder is used to prepare magnetic fluid, electromagnetic shielding material or catalyst.
[0077] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0078] The system refers to an equipment system, a device system or a production device.
[0079] Compared with the prior art, the present invention has the following beneficial effects:
[0080] The preparation method provided by the present invention adds modified micro silicon powder into the original iron-nickel alloy powder, thereby reducing the negative influence on the high saturation magnetic induction intensity performance of the micron-level magnetic powder, and effectively improving the resistivity of the iron-nickel alloy magnetic powder. The obtained micron-level magnetic powder has good insulation, low loss, high magnetic permeability, and excellent DC bias performance. The magnetic powder is easy to flow, which is conducive to subsequent pressing and molding. At the same time, the preparation process is simple, which is conducive to large-scale promotion and application. DETAILED DESCRIPTION
[0081] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0082] Example 1
[0083] The present embodiment provides a micron-sized iron-nickel alloy magnetic powder and a preparation method thereof, the preparation method comprising the following steps:
[0084] (1) obtaining a micron-sized iron-nickel alloy raw powder with an average particle size of 5 μm, wherein the iron content of the iron-nickel alloy raw powder is 49.4 wt %, the nickel content is 49.3 wt %, and the content of impurity metals is ≤1.3 wt %;
[0085] (2) Based on the mass of the iron-nickel alloy raw powder, 1.5 wt% of isocyanate silane was first added to 5 wt% of acetone and stirred to dissolve, and then 1.5 wt% of microsilica powder with an average particle size of 0.5 μm was added to the acetone and stirred evenly, the solvent was heated to 110° C., and 4 wt% of anhydrous ethanol was added dropwise while stirring until the solvent was completely volatilized to obtain modified microsilica powder;
[0086] (3) mixing the original iron-nickel alloy powder and the modified microsilicon powder and ball milling for 30 minutes, annealing in a nitrogen-hydrogen mixed atmosphere with a hydrogen volume fraction of 25%, and annealing at a temperature of 500° C. for 2 hours to obtain an intermediate powder;
[0087] (4.1) The intermediate powder is passivated, specifically comprising the following steps:
[0088] (4.1.1) Using the mass of the intermediate powder as a reference, 1 wt% phosphoric acid and 10 wt% acetone were mixed to obtain a passivation solution;
[0089] (4.1.2) mixing the intermediate powder and the passivation solution, stirring at 40°C for 5 min, and then heating to 120°C until the solvent is completely evaporated to obtain a passivation powder;
[0090] (4.2) Insulating and coating the passivated powder, specifically comprising the following steps:
[0091] (4.2.1) Based on the mass of the passivation powder, 2 wt% silicone resin, 0.4 wt% m-xylidine and 10 wt% acetone were mixed to obtain a bonding solution;
[0092] (4.2.2) Mix the passivation powder and the bonding solution, stir for 10 minutes, and then heat to 50° C. until the solvent is completely evaporated to obtain a bonding powder;
[0093] (4.2.3) Using the mass of the bonding powder as a reference, the bonding powder and 0.3 wt % aluminum stearate were mixed and ball-milled for 30 min to obtain micron-sized iron-nickel alloy magnetic powder.
[0094] Example 2
[0095] The present embodiment provides a micron-sized iron-nickel alloy magnetic powder and a preparation method thereof, the preparation method comprising the following steps:
[0096] (1) obtaining a micron-sized iron-nickel alloy raw powder with an average particle size of 4 μm, wherein the iron content of the iron-nickel alloy raw powder is 45 wt %, the nickel content is 53.5 wt %, and the content of impurity metals is ≤1.5 wt %;
[0097] (2) Based on the mass of the iron-nickel alloy raw powder, 1 wt% of isocyanate silane was first added to 4 wt% of acetone and stirred to dissolve, and then 1 wt% of microsilica powder with an average particle size of 1 μm was added to the acetone and stirred evenly, the solvent was heated to 100° C., and 2 wt% of anhydrous ethanol was added dropwise while stirring until the solvent was completely volatilized to obtain modified microsilica powder;
[0098] (3) mixing the original iron-nickel alloy powder and the modified microsilicon powder and ball milling for 20 minutes, annealing in a nitrogen-hydrogen mixed atmosphere with a hydrogen volume fraction of 20%, and annealing at a temperature of 400° C. for 4 hours to obtain an intermediate powder;
[0099] (4.1) The intermediate powder is passivated, specifically comprising the following steps:
[0100] (4.1.1) Using the mass of the intermediate powder as a reference, 0.5 wt% phosphoric acid and 8 wt% acetone were mixed to obtain a passivation solution;
[0101] (4.1.2) mixing the intermediate powder and the passivation solution, stirring at 30°C for 6 min, and then heating to 100°C until the solvent is completely evaporated to obtain a passivation powder;
[0102] (4.2) Insulating and coating the passivated powder, specifically comprising the following steps:
[0103] (4.2.1) Based on the mass of the passivation powder, 1 wt% epoxy resin, 0.3 wt% m-xylidine and 8 wt% acetone were mixed to obtain a bonding solution;
[0104] (4.2.2) mixing the passivation powder and the bonding solution, stirring for 8 minutes and then heating to 40° C. until the solvent is completely evaporated to obtain a bonding powder;
[0105] (4.2.3) Using the mass of the bonding powder as a reference, the bonding powder and 0.1 wt % zinc stearate were mixed and ball-milled for 20 min to obtain micron-sized iron-nickel alloy magnetic powder.
[0106] Example 3
[0107] The present embodiment provides a micron-sized iron-nickel alloy magnetic powder and a preparation method thereof, the preparation method comprising the following steps:
[0108] (1) obtaining a micron-sized iron-nickel alloy raw powder with an average particle size of 6 μm, wherein the iron content of the iron-nickel alloy raw powder is 53.5 wt %, the nickel content is 45 wt %, and the content of impurity metals is ≤ 1.5 wt %;
[0109] (2) Based on the mass of the iron-nickel alloy raw powder, 3 wt% of isocyanate silane was first added to 6 wt% of acetone and stirred to dissolve, and then 3 wt% of microsilica powder with an average particle size of 0.1 μm was added to the acetone and stirred evenly, the solvent was heated to 120° C., and 5 wt% of anhydrous ethanol was added dropwise while stirring until the solvent was completely volatilized to obtain modified microsilica powder;
[0110] (3) mixing the original iron-nickel alloy powder and the modified microsilicon powder and ball milling them for 40 minutes, and annealing them in a nitrogen-hydrogen mixed atmosphere with a hydrogen volume fraction of 22%, and the annealing temperature is 600° C., and the time is 1 hour to obtain an intermediate powder;
[0111] (4.1) The intermediate powder is passivated, specifically comprising the following steps:
[0112] (4.1.1) Using the mass of the intermediate powder as a reference, 2 wt% phosphoric acid and 12 wt% acetone were mixed to obtain a passivation solution;
[0113] (4.1.2) mixing the intermediate powder and the passivation solution, stirring at 50°C for 4 min, and then heating to 140°C until the solvent is completely evaporated to obtain a passivation powder;
[0114] (4.2) Insulating and coating the passivated powder, specifically comprising the following steps:
[0115] (4.2.1) Based on the mass of the passivation powder, 3 wt% phenolic resin, 0.5 wt% m-xylidine and 12 wt% acetone were mixed to obtain a bonding solution;
[0116] (4.2.2) Mixing the passivation powder and the bonding solution, stirring for 12 minutes, and then heating to 60° C. until the solvent is completely evaporated to obtain a bonding powder;
[0117] (4.2.3) Using the mass of the bonding powder as a reference, the bonding powder and 1 wt% graphite powder were mixed and ball-milled for 40 min to obtain micron-sized iron-nickel alloy magnetic powder.
[0118] Example 4
[0119] The present embodiment provides a micron-sized iron-nickel alloy magnetic powder and a preparation method thereof. In the preparation method, except that the amount of microsilicon powder in step (2) is changed to 0.8wt%, the remaining steps and conditions are the same as those in Example 1, and thus are not described in detail here.
[0120] Example 5
[0121] The present embodiment provides a micron-sized iron-nickel alloy magnetic powder and a preparation method thereof. In the preparation method, except that the amount of microsilicon powder in step (2) is changed to 3.5wt%, the remaining steps and conditions are the same as those in Example 1, and thus are not described in detail here.
[0122] Example 6
[0123] The present embodiment provides a micron-sized iron-nickel alloy magnetic powder and a preparation method thereof. In the preparation method, except that the temperature of the annealing treatment in step (3) is reduced to 300° C., the remaining steps and conditions are the same as those in Example 1, and thus are not described in detail here.
[0124] Example 7
[0125] The present embodiment provides a micron-sized iron-nickel alloy magnetic powder and a preparation method thereof. In the preparation method, except that the temperature of the annealing treatment in step (3) is reduced to 700° C., the remaining steps and conditions are the same as those in Example 1, and thus are not described in detail here.
[0126] Comparative Example 1
[0127] This comparative example provides a micron-sized iron-nickel alloy magnetic powder and a preparation method thereof. In the preparation method, except that isocyanate silane is not added in step (2), the remaining steps and conditions are the same as those in Example 1, and thus are not described in detail here.
[0128] Comparative Example 2
[0129] This comparative example provides a micron-sized iron-nickel alloy magnetic powder and a preparation method thereof. In the preparation method, except that anhydrous ethanol is not added for alcoholysis in step (2), the remaining steps and conditions are the same as those in Example 1, and thus are not described in detail here.
[0130] Comparative Example 3
[0131] This comparative example provides a micron-sized iron-nickel alloy magnetic powder and a preparation method thereof, the preparation method comprising the following steps:
[0132] (1) obtaining a micron-sized iron-nickel alloy raw powder with an average particle size of 5 μm, wherein the iron content of the iron-nickel alloy raw powder is 49.4 wt %, the nickel content is 49.3 wt %, and the content of impurity metals is ≤1.3 wt %;
[0133] (2) annealing the micron-sized iron-nickel alloy raw powder in a nitrogen-hydrogen mixed atmosphere with a hydrogen volume fraction of 25%, and the annealing temperature is 500° C. and the time is 2 h to obtain an intermediate powder;
[0134] (3.1) The intermediate powder is passivated, specifically comprising the following steps:
[0135] (3.1.1) Using the mass of the intermediate powder as a reference, 1 wt% phosphoric acid and 10 wt% acetone were mixed to obtain a passivation solution;
[0136] (3.1.2) mixing the intermediate powder and the passivation solution, stirring at 40°C for 5 min, and then heating to 120°C until the solvent is completely evaporated to obtain a passivation powder;
[0137] (3.2) Insulating and coating the passivated powder, specifically comprising the following steps:
[0138] (3.2.1) Based on the mass of the passivation powder, 2 wt% silicone resin, 0.4 wt% m-xylidine and 10 wt% acetone were mixed to obtain a bonding solution;
[0139] (3.2.2) mixing the passivation powder and the bonding solution, stirring for 10 minutes and then heating to 50° C. until the solvent is completely evaporated to obtain a bonding powder;
[0140] (3.2.3) Using the mass of the bonding powder as a reference, the bonding powder and 0.3 wt % aluminum stearate were mixed and ball-milled for 30 min to obtain micron-sized iron-nickel alloy magnetic powder.
[0141] Magnetic powder performance test:
[0142] Weigh 1.80±0.05g of micron-sized iron-nickel alloy magnetic powder and put it into a mold with an outer diameter of 12.70mm and an inner diameter of 7.6mm. 2 The formed magnetic ring is pressed into a ring under the conditions of , and the formed magnetic ring is annealed and cured for 1 hour in a nitrogen-hydrogen mixed atmosphere at 700°C and a hydrogen volume fraction of 25%; the cured magnetic ring is wound with 0.4mm high-temperature copper wire, with 20 inner circles and 20 outer circles; the inductance and 100Oe DC superposition inductance are measured under the test conditions of 100k / HZ, 1v, and the magnetic permeability and DC bias capability are calculated; the loss is obtained by testing under the test conditions of 1MHz, 50mT.
[0143] The test results of the iron-nickel alloy magnetic powders obtained in Examples 1-7 and Comparative Examples 1-3 are shown in Table 1 below:
[0144] Table 1
[0145] Iron-nickel alloy magnetic powder Magnetic permeability (H / m) DC superposition <![CDATA[Loss (Kw / m 3 )]]> Example 1 92.5 50% 1823 Example 2 88.6 48% 1763 Example 3 79.8 58% 1612 Example 4 94.1 48% 2563 Example 5 75.6 51% 1812 Example 6 69.4 49% 2353 Example 7 94.5 41% 7493 Comparative Example 1 73.8 48% 1789 Comparative Example 2 69.8 50% 1768 Comparative Example 3 95.7 38% 16235
[0146] From Table 1, we can see that:
[0147] (1) By comparing Example 1, Example 2 and Example 3, it is found that by changing the experimental objects and some conditions in the process within a suitable range, various magnetic powders with excellent performance and advantages can be coated to prepare magnetic powder cores with different requirements;
[0148] (2) By comparing Example 1 with Examples 4, 5, 6, and 7, it is found that improper experimental conditions, such as adding too little or too much microsilicon powder and using too low or too high annealing temperature, can ensure that some performance is not weakened, but will cause the overall performance of the magnetic powder core to be significantly reduced;
[0149] (3) By comparing Example 1 with Comparative Examples 1, 2, and 3, it is found that adding an appropriate amount of submicron microsilica powder modified by isocyanate silane hydrolysis with anhydrous ethanol can effectively increase the resistivity of the magnetic powder while ensuring the saturation magnetic induction intensity of the magnetic powder, thereby reducing the high-frequency loss of micron-level ultrafine iron-nickel powder and improving the DC superposition performance.
[0150] It can be seen that the preparation method provided by the present invention effectively improves the resistivity of the iron-nickel alloy magnetic powder while reducing the negative impact on the high saturation magnetic induction intensity performance of the micron-level magnetic powder by adding modified microsilicon powder to the iron-nickel alloy original powder. The obtained micron-level magnetic powder has good insulation, low loss, high magnetic permeability, and excellent DC bias performance. The magnetic powder is easy to flow, which is conducive to subsequent pressing and molding. At the same time, the preparation process is simple, which is conducive to large-scale promotion and application.
[0151] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing micron-sized iron-nickel alloy magnetic powder, characterized in that: The preparation method comprises the following steps: (1) obtaining an iron-nickel alloy raw powder having a particle size of micrometer level; (2) mixing a silane coupling agent, an organic solvent and microsilica powder, stirring them evenly, and then heating and performing alcoholysis until the solvent is completely volatilized to obtain modified microsilica powder; (3) mixing the original iron-nickel alloy powder and the modified microsilicon powder, ball milling, and annealing to obtain an intermediate powder; (4) performing a passivation treatment and an insulation coating on the intermediate powder in sequence to obtain a micron-sized iron-nickel alloy magnetic powder; There is no particular order in which steps (1) and (2) are performed.
2. The preparation method according to claim 1, characterized in that: The average particle size of the iron-nickel alloy raw powder in step (1) is 4-6 μm; Preferably, the iron content in the iron-nickel alloy raw powder in step (1) is 45-55wt%; Preferably, the nickel content in the iron-nickel alloy raw powder in step (1) is 45-55wt%; Preferably, the content of impurity metals in the iron-nickel alloy raw powder in step (1) is ≤1.5wt%.
3. The preparation method according to claim 1 or 2, characterized in that: The mixing method in step (2) includes: firstly adding the silane coupling agent into the organic solvent and stirring to dissolve, and then adding the microsilica powder into the organic solvent and stirring evenly; Preferably, based on the mass of the iron-nickel alloy raw powder, the amount of the silane coupling agent in step (2) is 1-3wt%; Preferably, based on the mass of the iron-nickel alloy raw powder, the amount of the organic solvent in step (2) is 4-6wt%; Preferably, based on the mass of the original iron-nickel alloy powder, the amount of the microsilicon powder in step (2) is 1-3wt%; Preferably, the silane coupling agent in step (2) comprises isocyanate silane; Preferably, the organic solvent in step (2) comprises acetone; Preferably, the average particle size of the microsilica powder in step (2) is 0.1-1 μm.
4. The preparation method according to any one of claims 1 to 3, characterized in that The method of heating alcoholysis in step (2) comprises: heating the uniformly stirred solvent to a target temperature, and adding anhydrous ethanol dropwise while stirring; Preferably, the target temperature is 100-120°C; Preferably, based on the mass of the iron-nickel alloy raw powder, the amount of anhydrous ethanol used is 2-5wt%.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The ball milling time in step (3) is 20-40 min; Preferably, the annealing treatment in step (3) is carried out in a nitrogen-hydrogen mixed atmosphere; Preferably, the volume fraction of hydrogen in the nitrogen-hydrogen mixed atmosphere is ≥20%; Preferably, the temperature of the annealing treatment in step (3) is 400-600°C; Preferably, the annealing treatment time in step (3) is 1-4 hours.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The passivation treatment in step (4) comprises the following steps: (4.1.1) mixing phosphoric acid and acetone to obtain a passivation solution; (4.1.2) mixing the intermediate powder and the passivation solution, stirring evenly, and heating to a first temperature until the solvent is completely volatilized to obtain a passivation powder; Preferably, the insulating coating in step (4) comprises the following steps: (4.2.1) mixing a binder, a curing agent and acetone to obtain a bonding solution; (4.2.2) mixing the passivation powder and the bonding solution, stirring evenly, and heating to a second temperature until the solvent is completely volatilized to obtain a bonding powder; (4.2.3) The mixed bonding powder and the release agent are ball-milled to obtain micron-sized iron-nickel alloy magnetic powder.
7. The preparation method according to claim 6, characterized in that: Based on the mass of the intermediate powder, the amount of phosphoric acid used in step (4.1.1) is 0.5-2wt%; Preferably, based on the mass of the intermediate powder, the amount of acetone used in step (4.1.1) is 8-12 wt %; Preferably, the stirring temperature in step (4.1.2) is 30-50°C; Preferably, the stirring time in step (4.1.2) is 4-6 min; Preferably, the first temperature in step (4.1.2) is 100-140°C; Preferably, based on the mass of the passivation powder, the amount of the binder in step (4.2.1) is 1-3wt%; Preferably, based on the mass of the passivation powder, the amount of the curing agent in step (4.2.1) is 0.3-0.5wt%; Preferably, based on the mass of the passivation powder, the amount of acetone used in step (4.2.1) is 8-12 wt %; Preferably, the adhesive in step (4.2.1) comprises any one of epoxy resin, silicone resin or phenolic resin, or a combination of at least two thereof; Preferably, the curing agent in step (4.2.1) comprises m-xylidine; Preferably, the stirring time in step (4.2.2) is 8-12 min; Preferably, in step (4.2.2), the second temperature is 40-60°C; Preferably, based on the mass of the bonding powder, the amount of the release agent in step (4.2.3) is 0.1-1wt%; Preferably, the release agent in step (4.2.3) comprises any one of zinc stearate, magnesium stearate, aluminum stearate, calcium stearate or graphite powder, or a combination of at least two thereof; Preferably, the ball milling time in step (4.2.3) is 20-40 min.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) obtaining a micron-sized iron-nickel alloy raw powder with an average particle size of 4-6 μm, wherein the iron content of the iron-nickel alloy raw powder is 45-55 wt %, the nickel content is 45-55 wt %, and the content of impurity metals is ≤1.5 wt %; (2) Based on the mass of the iron-nickel alloy raw powder, 1-3wt% of isocyanate silane is first added to 4-6wt% of acetone and stirred to dissolve, and then 1-3wt% of microsilica powder with an average particle size of 0.1-1μm is added to the acetone and stirred evenly, the solvent is heated to 100-120°C, and 2-5wt% of anhydrous ethanol is added dropwise while stirring until the solvent is completely volatilized to obtain modified microsilica powder; (3) mixing the original iron-nickel alloy powder and the modified microsilicon powder and ball milling for 20-40 minutes, annealing in a nitrogen-hydrogen mixed atmosphere with a hydrogen volume fraction of ≥20%, and the annealing temperature is 400-600° C., and the time is 1-4 hours to obtain an intermediate powder; (4.1) The intermediate powder is passivated, specifically comprising the following steps: (4.1.1) Based on the mass of the intermediate powder, 0.5-2 wt % phosphoric acid and 8-12 wt % acetone are mixed to obtain a passivation solution; (4.1.2) mixing the intermediate powder and the passivation solution, stirring at 30-50° C. for 4-6 minutes, and then heating to 100-140° C. until the solvent is completely evaporated to obtain a passivation powder; (4.2) Insulating and coating the passivated powder, specifically comprising the following steps: (4.2.1) Based on the mass of the passivation powder, 1-3 wt% of a binder, 0.3-0.5 wt% of m-xylidine and 8-12 wt% of acetone are mixed to obtain a bonding solution; the binder comprises any one of epoxy resin, silicone resin or phenolic resin or a combination of at least two thereof; (4.2.2) mixing the passivation powder and the bonding solution, stirring for 8-12 minutes and then heating to 40-60° C. until the solvent is completely evaporated to obtain a bonding powder; (4.2.3) Based on the mass of the bonding powder, the bonding powder and 0.1-1wt% of a release agent are mixed and ball-milled for 20-40 minutes to obtain micron-sized iron-nickel alloy magnetic powder; the release agent comprises any one of zinc stearate, magnesium stearate, aluminum stearate, calcium stearate or graphite powder, or a combination of at least two thereof; There is no particular order in which steps (1) and (2) are performed.
9. A micron-sized iron-nickel alloy magnetic powder, characterized in that: The micron-sized iron-nickel alloy magnetic powder is prepared by the preparation method as described in any one of claims 1 to 8.
10. An application of the micron-sized iron-nickel alloy magnetic powder as claimed in claim 9, characterized in that: The micron-sized iron-nickel alloy magnetic powder is used for preparing magnetic fluid, electromagnetic shielding material or catalyst.
Citation Information
Patent Citations
Composite coating method for low-loss iron-nickel magnetic powder core
CN114156034A
Low-loss iron-nickel soft magnetic powder and preparation method thereof
CN115985614A